Diagnostic Challenges in Uncommon Firearm Injury Cases: A Multidisciplinary Approach - Andrea Vittorio Maria Failla; Gabriele Licciardello; Giuseppe Cocimano; Lucio Di Mauro; Mario Chisari; Francesco Sessa; Monica Salerno; Massimiliano Esposito (Diagnostics, 2024)
Background: Firearm wounds tend to have a precise pattern. Despite this, real-world case presentations can present uncertain elements, sometimes deviating from what is considered standard, and present uncommon features that are difficult for forensic pathologists and ballistic experts to explain. Methods: A retrospective analysis of autopsy reports from the Institute of Legal Medicine, University of Catania, covering 2019–2023, included 348 judicial inspections and 378 autopsies performed as part of the institute’s overall activities. Among these, seventeen cases of firearm deaths were identified, with three atypical cases selected for detailed analysis. An interdisciplinary approach involving forensic pathology, radiology, and ballistics was used. Results: The selected cases included: (1) A 56-year-old female with a thoracic gunshot wound involving three 7.65 caliber bullets, displaying complex trajectories and retained bullets; (2) A 48-year-old male with two cranial gunshot injuries, where initial evaluation suggested homicide staged as a suicide, later confirmed to be a single self-inflicted shot; and (3) A 51-year-old male was found in a car with two gunshot wounds to the head, involving complex forensic evaluation to distinguish between entrance and exit wounds and determine trajectory. The findings showed significant deviations from standard patterns, underscoring the critical role of radiological imaging and ballistic analysis in understanding wound morphology and projectile trajectories. Conclusions: This case series highlights the necessity for standardized yet adaptable protocols and cooperation among forensic specialists. A flexible approach allows forensic investigations to be tailored to the specific circumstances of each case, ensuring that essential examinations are conducted while unnecessary procedures are avoided. Comprehensive data collection from autopsies, gross organ examinations, and, when needed, radiological and histological analysis is essential to accurately diagnose injuries, trace bullet trajectories, retrieve retained projectiles, and determine the fatal wound, particularly in complex cases or those involving multiple shooters.